ANAPHORIC AND CATAPHORIC REFERENCES USED IN THE CHAPEL SHORT STORY - Ana Shofiana Jamilah; Agnes Larasati; Luthfi Nasiroh Khoirun Nisa (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2023)
This study aims to analyze the endophoric reference including the types of Anaphora and cataphoric reference that are contained in the short story titled "The Chapel". The researcher uses the descriptive qualitative method to analyze the selection of endophoric reference including the types of Anaphora and cataphoric reference. The data is in the form of a script of "The Chapel" short story. The technique of collecting data by reading the The Chapel short story and then marking words according to the types of anaphoric and cataphoric. The results showed there are 45 anaphoric references and 5 cataphoric references found in the short story.